3362 Enhancing Mentee Motivation Using the CARES Mentoring Model: A New Online Mentor Training Module. (27th March 2019) - Weber-Main, Anne Marie; Shanedling, Janet; Lapsitis, Roberta; LaGuardia, Jennifer
Abstract : OBJECTIVES/SPECIFIC AIMS: The goals of this project are to develop, disseminate, and evaluate an online, self-paced training module designed to help mentors better understand and support their mentees' motivation. The module introduces learners to the CARES mentoring model, which is rooted in Self-Determination Theory (SDT), one of the leading theories of motivation. According to SDT, an optimal mentoring environment provides support for mentees' psychological needs for Competence, Autonomy, Relatedness, Equity in extrinsic resources, and Structure (CARES). METHODS/STUDY POPULATION: Content for the CARES online module was drawn from a previously developed two-hour mentor training workshop designed for delivery in a face-to-face, small group setting. Content experts developed a slide deck and speaker notes. These materials were edited, adapted into a storyboard, and translated into a 60-minute interactive online module created with e-learning authoring software (Articulate Storyline). An evaluation survey was developed to assess mentors' perceived skills gains related to course content (e.g., "Encouraging my mentees to think about how well their psychological needs are being met within the work/training environment, " "Recognizing how diversity, equity, and inclusion can be salient issues that impact a mentee's motivation") and mentors' confidence gains in their ability to implement motivation-focused practices into their mentoring relationships (e.g., "Autonomy: Giving my mentees freedom in deciding what goals to pursue and how they to do their work, " "Competence: Working with my mentees to establish appropriate challenges to stretch their abilities"). The module was beta tested in October 2018 by 11 individuals with experience as mentors and in facilitating mentor training. RESULTS/ANTICIPATED RESULTS: The beta testing process produced useful recommendations for improving clarity of content, visual design, and navigation. Users expressed a high level of enthusiasm for the content, which included a combination of practical information and empirical support for the CARES mentoring model. They also appreciated specific functionality in the module, including the presentation of brief case examples of mentoring scenarios that enhance or diminish motivation, opportunities for self-reflection, and a downloadable guide for initiating conversations with mentees about different domains in the CARES model. Evaluation data (quantitative and qualitative) from beta testers (n=11) are being analyzed. A preliminary examination of these findings found that mentors report gains from before to after the training in their self-perceived skills and confidence levels. Moreover, all expressed an intention to makes changes in their mentoring practices as a result of the training. Comments indicated potential value in offering a follow up face-to-face experience in which mentors can hear from others who have successfully implemented the CARES approach and acquire practice in skillfully implementing the CARES conversation guide with their mentees. DISCUSSION/SIGNIFICANCE OF IMPACT: This innovative e-learning module offers a readily accessible and theoretically driven training approach to help mentors recognize the value of supporting their mentees' motivation, and become more intentional in implementing motivation-focused practices into their mentoring relationships. In future work, the CARES module will be pilot tested with specific cohorts and in different implementation scenarios (as a standalone training, or combined with other programming) and made available to users nationally with support from the University of Minnesota Clinical and Translational Science Institute and the NIH National Research Mentoring Network.